Assessing the Toxic Levels in Parenting Behavior and Coping Strategies Implemented During the COVID-19 Pandemic - Pratiwi, Hardiyanti; Yarliani, Ikta; Ismail, Murniyanti; Haida, Rizki Noor; Asmayanti, Noer (Program Studi Magister Pendidikan Anak Usia Dini, 2020)
The COVID-19 pandemics have caused a lot of stressors for parents. Apart from doing daily activities, parents also have to take care of their children and accompany them to study. The number of stressors can lead to toxic behavior in parenting. This study aims to measure the level of toxicity in parenting behavior and coping strategies adopted by parents. This study uses quantitative descriptive methods to measure toxic levels in parenting behavior during the COVID-19 pandemic. A total of 568 parents from Banjarmasin and Yogyakarta participated in this study. The survey results show that several factors can trigger parenting stress during the COVID-19 pandemic, namely worsening economic conditions, delinquent children, excessive anxiety, accumulated daily hassles, growing family demands, and disputes with spouses. However, some of these stressors do not lead to toxic parenting. The results showed that 97.79% of respondents from Banjarmasin and 95.29% from Yogyakarta showed a low toxic level. The remaining 2.21% of respondents in Banjarmasin and 4.71% of respondents in Yogyakarta indicated a moderate toxic level. Coping strategies are crucial for neutralizing stress. There are several strategies applied, namely trying to consider a problem is God's test, and there is a positive side to every problem; trying to address the source of stress and solving it; Withdrawing and finding individual time; looking for social support from the family and others; crying and releasing it by doing favorite things and capitulate and get back the problem. This Research is expected to be a reference for parents in choosing coping strategies to manage the stress they feel in parenting during the pandemic. Keywords: Toxic parenting; stress trigger, coping strategy; COVID-19 References Abidin, R. R. (1990). Parenting Stress Index (PSI) manual. Psychological Assessment Resources, Inc. Anthony, L. G., Anthony, B. J., Glanville, D. N., Naiman, D. Q., Waanders, C., & Shaffer, S. (2005). The Relationships Between Parenting Stress, Parenting Behaviour and Preschoolers’ Social Competence and Behaviour Problems in the Classroom. Infant and Child Development, 14(2), 133–154. https://doi.org/10.1002/icd Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Asdi Mahasatya. Badanes, L. S., Dmitrieva, J., & Watamura, S. E. (2012). Understanding cortisol reactivity across the day at child care: The potential buffering role of secure attachments to caregivers. Early Childhood Research Quarterly, 27(1), 156–165. https://doi.org/10.1016/j.ecresq.2011.05.005 Belsky, J. (2005). Social-contextual determinants of parenting. In Encyclopaedia on early childhood development. Berlin, L. ., Appleyard, K., & Dodge, K. . (2011). Intergenerational continuity in child maltreatment: mediating mechanisms and implications for prevention. Child Development, 82, 162–176. https://doi.org/10.1111/j.14678624.2010.01547.x Bethell, C. D., Newacheck, P., Hawes, E., & Halfon, N. (2014). Adverse childhood experiences: assessing the impact on health and school engagement and the mitigating role of resilience. Health Affairs, 33(12), 2106–2115. https://doi.org/10.1377/hlthaff.2014.0914 Branco, M. S. S., & Linhares, M. B. M. (2018). The toxic stress and its impact on development in the Shonkoff’s Ecobiodevelopmental Theorical approach. Estudos de Psicologia (Campinas), 35(1), 89–98. https://doi.org/10.1590/1982-02752018000100009 Braveman, A. P. (2009). Health disparities beginning in childhood: A life-course perspective. Pediatrics, 124. https://doi.org/10.1542 Caldwell, J. ., Shaver, P. ., Li, C., & Minzenberg, M. . (2011). Childhood maltreatment, adult attachment and depression as predictors of parental self-efficacy in at-risk mothers. Journal Aggress Maltreat Trauma, 20, 595–616. https://doi.org/10.1080/10926771.2011.595763 Cohan, S. ., Jang, K. ., & Stein, M. . (2006). Conﬁrmatory factor analysis of a Short Form of the Coping Inventory for Stressful Situations. Journal of Clinical Psychology, 62. Corrigan, P., McCorkle, B., Schell, B., & Kidder, K. (2003). Religion and spirituality in the lives of people with serious mental illnes. Community Mental Health Journal, 39(6). Crnic, K. ., Gaze, C., & Hoffman, C. (2005). Cumulative parenting stress across the preschool period: relations to maternal parenting and child behavior at age 5. Infant and Child Development, 14, 117–132. https://doi.org/10.1002/icd.384 Daulay, N. (2018). Parenting Stress of Mothers in Children with Autism Spectrum Disorder: A Review of the Culture in Indonesia. KnE Social Sciences, 3(5), 453. https://doi.org/10.18502/kss.v3i5.2349 Davis, N. O., & Carter, A. S. (2008). Parenting stress in mothers and fathers of toddlers with autism spectrum disorders: Associations with child characteristics Disorders. Journal of Autism Developmental, 38, 1278–1291. Deater-deckard, K. (1998). Parenting Stress and Child Adjustment : Some Old Hypotheses and New Questions. Clinical Psychology Science and Practice, 5(3). Deckard, K. D.-, & Scarr, S. (1996). Parenting stress among the dual-earner mothers and fathers: are there gender differences? Journal of Family Psychology, 10, 45–59. https://doi.org/10.1037/0893-3200.10.1.45 Dunham, S., & Dermer, H. (2011). Poisonous Parenting : Toxic Relationships Between Parents And Their Adult. Routledge Taylor & Francis Group. Ekas, N., & Whitman, T. L. (2010). Autism symptom topography and maternal socioemotional functioning. American Journal on Intellectual and Developmental Disabilities, 115(3), 234–249. Felitti, V. J., Anda, R. F., Nordenberg, D., Williamson, D. F., Spitz, A. M., Edwards, V., Koss, M. P., & Marks, J. S. (1998). Household Dysfunction to Many of the Leading Causes of Death in Adults The Adverse Childhood Experiences ( ACE ) Study. 14(4), 245–258. Fitzgerald, M. ., Shipman, K. ., Jackson, J. ., McMahon, R. ., & Hanley, H. . (2005). Perceptions of parenting versus parent–child interactions among incest survivors. Child Abuse Negl, 29, 661–681. https://doi.org/10.1016/j.chiabu.2004.10.012 Gottman, J. M., & Silver, N. (1999). The seven principles for making marriage work. Three Rivers Press. Juster, R. P., McEwen, B. S., & Lupien, S. J. (2010). Allostatic load biomarkers of chronic stress and impact on health and cognition. Neuroscience and Biobehavioral Review, 35(1), 2–16. https://doi.org/10.1016 K., J., Margaret, M., & Disiye, A. (2020). Toxic Parenting Adversely Correlates To Students’ Academic Performance In Secondary Schools In Uasin Gishu County, Kenya. International Journal of Scientific and Research Publications (IJSRP),10(7), 249–253. https://doi.org/10.29322/ijsrp.10.07.2020.p10331 Koeske, G. F., & Koeske, R. D. (1990). The Buffering Effect Of Social Support On Parental Stress. American Journal of Orthopsychiatry, 60(3). Kuczynski, L., & Kochanska, G. (1990). Development of children’s non-compliance strategies from toddlerhood to age 5. Developmental Psychology, 26, 8–408. Lazarus, R. S. (1993). Coping theory and research: Past, present, and future. Psychosomatic Medicine, 55, 234–247. Mash, E. J., & Johnston, C. (1990). Determinants of parenting stress: Illustrations from families of hyperactive children and families of physically abused children. Journal of Clinical Child Psychology, 19, 313–328. Mikulincer, M., Shaver, P. R., Bar-on, N., & Ein-dor, T. (2010). The Pushes and Pulls of Close Relationships : Attachment Insecurities and Relational Ambivalence. PS Sozialpsychologie, 98(3), 450–468. Mortensen, J. A., & Barnet, M. A. (2020). The role of child care in supporting the emotion regulatory needs of maltreated infants and toddlers. The University of Arizona. National Academies of Sciences, Engineering, and M. (2016). Parenting Matters: Supporting Parents of Children Ages 0-8. The National Academies Press. https://doi.org/doi:10.17226/21868 National Scientiﬁc Council on the Developing Child. (2007). Key concepts: toxic stress. National Scientiﬁc Council on the Developing Child. Ostberg, M., & Hagekull, B. (2000). A structural modeling approach to the understanding of parenting stress. Journal of Clinical Child Psychology, 29, 615–625. Pediatrics, A. A. of. (2018). ACEs and toxic stress. American Academy of Pediatrics. Rodenburg, R., Meijer, A. M., Dekovic, M., & Aldenkamp, A. (2007). Parents of children with enduring epilepsy: Predictors of parenting stress and parenting. Epilepsy & Behavior, 11, 197–207. Shonkoff, J. P., Garner, A. S., Siegel, B. S., Dobbins, M. I., Earls, M. F., McGuinn, L., & Wood, D. L. (2012). The lifelong effects of early childhood adversity and toxic stress. Pediatrics, 129(1), 232–246. https://doi.org/10.1542 Shonkoff, J.P. (2012). Leveraging the biology of adversity to address the roots of disparities in health and development. Proceedings of the National Academy of Sciences of the United States of America, 109(SUPPL.2), 17302–17307. https://doi.org/10.1073/pnas.1121259109 Shonkoff, Jack P., & Bales, S. N. (2011). Science Does Not Speak for Itself: Translating Child Development Research for the Public and Its Policymakers. Child Development, 82(1), 17–32. https://doi.org/10.1111/j.1467-8624.2010.01538.x Shonkoff, Jack P., & Levitt, P. (2010). Neuroscience and the Future of Early Childhood Policy: Moving from Why to What and How. Neuron, 67(5), 689–691. https://doi.org/10.1016/j.neuron.2010.08.032 Shonkoff, Jack P. (2010). Building a New Biodevelopmental Framework to Guide the Future of Early Childhood Policy. 81(1), 357–367. Shonkoff, Jack P, & Fisher, P. A. (2013). Rethinking evidence-based practice and two-generation programs to create the future of early childhood policy. 25, 1635–1653. https://doi.org/10.1017/S0954579413000813 Shonkoff, Jack P, Richter, L., Gaag, J. Van Der, Bhutta, Z. A., Shonkoff, A. J. P., & Richter, L. (2012). An Integrated Scienti fi c Framework for Child Survival and Early Childhood Development. Pediatrics. https://doi.org/10.1542/peds.2011-0366 Siegel, B. S., Dobbins, M. I., Earls, M. F., Garner, A. S., Pascoe, J., Wood, D. L., High, P. C., Donoghue, E., Fussell, J. J., Gleason, M. M., Jaudes, P. K., Jones, V. F., Rubin, D. M., Schulte, E. E., Macias, M. M., Bridgemohan, C., Goldson, E., McGuinn, L. J., Weitzman, C., & Wegner, L. M. (2012). Early childhood adversity, toxic stress, and the role of the pediatrician: Translating developmental science into lifelong health. Pediatrics, 129(1). https://doi.org/10.1542/peds.2011-2662 Slopen, N., Mclaughlin, K. A., & Shonkoff, J. P. (2014). Interventions to Improve Cortisol Regulation in Children : A Systematic Review abstract. https://doi.org/10.1542/peds.2013-1632